2008
DOI: 10.1007/s12011-007-8085-4
|View full text |Cite
|
Sign up to set email alerts
|

Study of Salivary Strontium and Silver Concentrations in Primary School Children Related to Dental Caries

Abstract: To investigate the relationship between the salivary Sr and Ag concentrations and tooth conditions, saliva was collected from 521 primary school children in Kitakyushu. The salivary Sr and Ag levels were determined using an atomic absorption spectrophotometry. The salivary Sr and Ag levels were 7.73 +/- 3.62 and 0.03 +/- 0.15 ng/ml, respectively, in the sound teeth group. No sex differences were noted in either element level, nor were there differences between the lower and upper grade groups. In the caries te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Blood concentration of strontium, phosphate and fluorine was significantly lower in patients with high carious activity in comparison with patients with low carious activity [12]. In saliva, the concentration of strontium was higher in children with caries experience in comparison to the saliva concentration of strontium in children with sound teeth and fluorine was found to inhibit strontium dissolution from teeth during carious attack [13]. Strontium and fluorine can be found in glass-ionomer cements used for bases or restorations of primary and permanent teeth.…”
Section: Introductionmentioning
confidence: 93%
“…Blood concentration of strontium, phosphate and fluorine was significantly lower in patients with high carious activity in comparison with patients with low carious activity [12]. In saliva, the concentration of strontium was higher in children with caries experience in comparison to the saliva concentration of strontium in children with sound teeth and fluorine was found to inhibit strontium dissolution from teeth during carious attack [13]. Strontium and fluorine can be found in glass-ionomer cements used for bases or restorations of primary and permanent teeth.…”
Section: Introductionmentioning
confidence: 93%
“…Curzon [1984] was able to demonstrate a weak, negative relationship between [Sr] in saliva andon caries prevalence (r = -0.13) in 105 children aged 14 years. In contradiction, during one very recent study [Shigemi et al, 2008] on 521 children aged 6 to 12 years was able to demonstrate a positive correlation between [Sr] in saliva and using the author's terminology 'caries experience' (no DMFT/S scores were recorded) was reported. In addition, the authors showed that in groups with high 'fluoride experience rates' (due to F mouth rinsing at school), [Sr] in saliva tended to be lower.…”
Section: Epidemiological Caries Studiesmentioning
confidence: 89%
“…Other studies concerning caries susceptibility with the relation to trace metal concentration in saliva of primary school children have been performed [75]. Additional field of the assessment of exposure to trace elements discussed in the literature were teeth, evaluated to reveal the relation of tooth element content of diabetics and hypertensives [76].…”
Section: Discussionmentioning
confidence: 99%